2016
DOI: 10.1186/s41100-016-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of heparin-induced thrombocytopenia (HIT) triggered by methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia

Abstract: Background: Heparin-induced thrombocytopenia (HIT) is a potentially life-threatening complication of heparin anticoagulation. Recently, infection has been implicated in the development of HIT. Case presentation: We herein present a case of HIT diagnosed by a repeated functional assay. A 67-year-old female with diabetic nephropathy was admitted to our hospital with hypoxemia caused by volume overload. Due to her diuretic-resistant condition, dialysis therapy anticoagulated with low-molecular-weight heparin (LMW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…A study by Grigorian and colleagues [78] found a higher frequency of HIT in patients who had bacterial infection, including the subsets of patients with urinary tract infection and pneumonia. One group presented a case of thrombocytopenia in the setting of heparin exposure and bacteremia with methicillin-susceptible Staphylococcus aureus, arguing that the bacteremia may have contributed to the clinical picture of HIT [79]. Sartori et al [80] found somewhat increased levels of anti-PF4/PVS antibodies in septic patients versus controls, although there was no difference in IgGspecific antibodies.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A study by Grigorian and colleagues [78] found a higher frequency of HIT in patients who had bacterial infection, including the subsets of patients with urinary tract infection and pneumonia. One group presented a case of thrombocytopenia in the setting of heparin exposure and bacteremia with methicillin-susceptible Staphylococcus aureus, arguing that the bacteremia may have contributed to the clinical picture of HIT [79]. Sartori et al [80] found somewhat increased levels of anti-PF4/PVS antibodies in septic patients versus controls, although there was no difference in IgGspecific antibodies.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%